Cheese Stories: Cheesemongers, Vermont Artisan Cheese and the Value of Telling Stories - DiStefano, Rachel; Trubek, Amy (Cuizine)

(untitled) (McGill University Library, 2015)
Vermont artisan cheese increasingly travels long distances to consumers. In these elongated supply chains highly specialized retail professionals known as cheesemongers occupy a pivotal position between consumers and producers. Ethnographic research among cheesemongers in different professional settings reveals the importance of shortening the distance between producer and consumer. We found that cheesemongers’ practice of telling specialized narratives called cheese stories creates social proximity, such that consumers are able to better understand the values and intentions of Vermont artisan cheesemakers and, potentially, feel a connection to them. While cheese retail professionals appear to agree that a certain level of intrinsic quality makes a difference to them and their customers, many also see the importance of, and derive pleasure from, knowing and conveying the story, and perceive this to be an important part of their professional role and identity.